Layered Topological Insulators and Semimetals for Magnetoresistance Type Sensors. Issue 1 (13th December 2018) - Zhang, Minhao; Wang, Xuefeng; Song, Fengqi; Zhang, Rong
Abstract: Magnetoresistance (MR) type sensors are transducers that can vary their resistances sensitively in response to an applied magnetic field. Recently, topological quantum materials have drawn the increased attention for sensor applications due to their novel MR effects. Here, a range of MR effects occurring in the layered 3D topological insulators and topological semimetals are briefly reviewed. The MR effects include the extremely large nonsaturating MR, the giant anisotropic MR, and the unique spin‐valve‐like MR. The large MR ratios, the high MR anisotropy, and the low 1/ f noise allow sensors to have the high sensitivity over a wide range of temperatures and magnetic fields. It is anticipated that the layered topological quantum materials with their excellent MR performance and structural flexibility would provide an ideal platform for new‐generation magnetic sensor applications. Abstract : Topological quantum materials with nontrivial band topology have exhibited novel magnetoresistance (MR) and drawn great attention in MR type sensors. This review provides an overview of a wide range of novel MR phenomena based on the layered topological materials, such as nonsaturating linear MR, anisotropic MR, and spin‐valve‐like tunneling MR. The perspectives for applications in new‐generation magnetic sensors are highlighted.